The Influence of E-commerce Use, Entrepreneurial Knowledge, and Entrepreneurial Motivation on Entrepreneurial Interest - Firdaus, Alfisya Putri; Mustika Dewi, Retno (Sumber Belajar Sejahtera, 2024)
Entrepreneurial activity is one solution to reduce a country's unemployment rate, and has the potential to improve the country's economy. However, in reality there is a problem where teenagers' interest in entrepreneurship is currently still relatively low. The aim of this research is to analyze the influence of e-commerce use, entrepreneurial knowledge, and entrepreneurial motivation on entrepreneurial interest. This research uses a saturated sampling technique with a sample of 143 teenagers in Mojokerto with a causal associative research method using a quantitative approach and multiple linear regression analysis with the help of IBM SPSS version 25 software. The results of the research show that simultaneously, the use of e-commerce, entrepreneurial knowledge and motivation entrepreneurship influences interest in entrepreneurship. Meanwhile, partially, the use of e-commerce and entrepreneurial motivation influence entrepreneurial interest, while entrepreneurial knowledge does not influence entrepreneurial interest. It is hoped that the results of this research can provide input to families and schools to provide support that can support teenagers' interest in entrepreneurship so that they have the courage to open new businesses.